EPCO-16. ONCOHISTONE INTERACTOME PROFILING UNCOVERS MECHANISMS OF CHROMATIN DISRUPTION AND IDENTIFIES POTENTIAL THERAPEUTIC TARGETS IN PEDIATRIC HIGH-GRADE GLIOMA. (12th November 2021) - Siddaway, Robert; Canty, Laura; Pajovic, Sanja; Coyaud, Etienne; Milos, Scott; Sbergio, Stefanie-Grace; Lubanszky, Evan; Yun, Haley; Carette, Sheyenne; Portante, Alessia; Raught, Brian; Campos, Eric; et al.
Abstract: Mutations in histone H3 at amino acids 27 (H3K27M) and 34 (H3G34R) occur with high-frequency in pediatric high-grade glioma. H3K27M mutations have been shown to lead to global disruption of H3K27me3 through dominant negative PRC2 inhibition with accompanying gains in H3K36me3, while H3G34R mutations lead to local losses of H3K36me3 through inhibition of SETD2. However, the mechanism of action of these mutants on the broader landscape of chromatin-associated proteins remains unknown. Importantly, proteins with differential associations with oncohistones could be targeted therapeutically. Here we profiled the interactomes of the H3.1K27M, H3.3K27M and H3.3G34R oncohistones using BioID to gain an unbiased measure of their interaction landscapes. Among the differential interactors all 3 mutants lost interaction with H3K9 methyltransferases, while H3G34R also had reduced interaction with DNA methyltransferases accompanied by genome-wide DNA hypomethylation. In contrast, H3K27M mutants had increased association with transcription factors, consistent with the activation of transcription induced by the global loss of H3K27me3. H3K9me3 was reduced in H3K27M-containing nucleosomes, and cis -H3K9 methylation was required for H3K27M to exert its effect on global H3K27me3. Depletion of H3K9 methyltransferases with shRNA or treatment with H3K9 methyltransferase inhibitors was lethal to H3.1K27M, H3.3K27M and H3.3G34R mutant pHGG cell lines, underscoring the importance of H3K9 methylation for oncohistone-mutant gliomas and suggesting it could make an attractive therapeutic target.